PENELITIAN SOSIAL DALAM RANGKA MENINGKATKAN EFEKTIVITAS PROGRAM CSR DI DESA SEGAMIT STUDI KASUS PT. SUPREME ENERGY - Mohammad Kurniawan (Universitas Indo Global Mandiri)
This research was conducted to find out anything the needs of the people who reside adjacent to Businesses around the site . In this case the company is close to settlements is PT . Supreme Energy engaged in the development of Geothermal Power in the village and surrounding Segamit .The purpose of this study , in addition to the needs of the community around PT . Supreme also to know how the impact and role of the presence of these companies in implementing Corporate Social Responsibility (CSR) to Segamit village and surrounding communities , and the study was conducted in Segamit village and surrounding villages are in MuaraEnim , South Sumatra Province